Life after career activities of the well-elderlies of Teacher's Village East and West Senior Citizens Association - Babela, Aya Daisa dela Torre; Decano, Aila Martha dela Cruz.; Tongson, Excelsa C. (2009.)
ABSTRACT The present study aimed to describe and categorize the various activities done by the well-elderlies in substitute for their previous work. 42 male and female well-elderlies from Teacher's Village East and West Senior Citizens Association. aged 65 and above were purposively selected to be the participants of the survey. 34 of these proceeded to participate in the two focus group discussion. Data obtained from these two methodologies were analyzed by using descriptive statistical analysis. The data from the focus group discussions supported those from the survey. From the results, six themse were developed by the researchers and health-related activities had the highest count. The respondents also showed high preference to do their activities with their family and peers. Only females answered activities falling under the household-related tasks. It is recommended that the general population of the elderly should be encouraged to actively participate in many activities that provide enjoyment and fulfillment in the retirement years. Future studies can employ a larger number of respondents, use a more sophisticated statistical analysis and interview, and concentrate on more specific dimensions of retirement.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Older people -- Philippines -- Quezon City